The Accuracy of Drivers' Judgments of the Effects of Headlight Glare on Their Own Visual Acuity. (November 2014) - Sewall, Ashley A Stafford; Borzendowski, Stephanie A Whetsel; Tyrrell, Richard A
Drivers' judgments of the magnitude of disability glare caused by high-beam headlights may not match actual declines in visual performance. This study investigated younger and older drivers' beliefs about their own visual performance in the presence of headlight glare. Eleven older drivers and seventeen younger drivers judged the distance at which they would just be able to recognize the orientation of a white Landolt C if it were present adjacent to the headlamps of a stationary opposing vehicle at night. The younger participants were generally accurate in their estimates of the recognition distance of the stimulus, while older participants significantly overestimated both their own acuity and the effect of glare on their vision. From this study, we see that older drivers' judgments about the disabling effects of oncoming headlights may be systematically inaccurate. These misperceptions about headlight glare may help explain why drivers tend to underuse high beams.